INOVASI PROGRAM GONE-DES UNTUK MENINGKATKAN KUALITAS PELAYANAN PUBLIK KECAMATAN GARUNG KABUPATEN WONOSOBO - ROCHMAH, ALIF VANESIA ELVINA; Yuwono, Teguh (Journal of Politic and Government Studies, 2020)
Public services are an inseparable part of the state for the welfare of its peopleand are the basic essence for the realization of social justice. Wanting a period ofdevelopment, public services are carried out with various forms of innovation. Innovationis the key to success in an organization, where without innovation the organization willnot develop. This innovation supports to improve the quality of public services. Thereforethis research aims to study and analyze the innovation of the Gone-Des ball drive toimprove the quality of public services in Garung Wonosobo District .The research method used in this study is a qualitative descriptive method, withdata collection techniques in the form of observation, interviews, questionnaires anddocumentation. The data obtained were then analyzed using triangulation of sources andmethods.The results of the study show that the Gone-Des innovation program in GarungSubdistrict provides convenience to the community where in one tempo of communityservice can obtain population documents, legalize business, and increase publicawareness and participation that improve the quality of public services provided by thedistrict. The Gone-Des innovation program as a way of issuing bureaucracy serves thepublic and can realize the responsive government of the Garung District. In addition,consciously, the community has participated in understanding the meaning of thechanges that occur, the community also helped positively to the changes that exist so asto make the Gone-Des program innovation able to survive and accept its environment.Thus, the program that is present Gone-Des can continue provide positive innovation inthe community.Keywords: Public Services, Innovation, Community Participation, ResponsiveGovernance